Splenic switch off as a novel marker for adenosine response in 13N-ammonia PET myocardial perfusion imaging – a pilot study. (25th November 2020) - Bakula, A; Patriki, D; Von Felten, E; Benetos, G; Sustar, A; Benz, D.C; Wiedemann-Buser, M; Treyer, V; Pazhenkottil, A.P; Graeni, C; Gebhard, C; Kaufmann, P.A; et al.
Abstract: Background: Positron emission tomography myocardial perfusion imaging (PET MPI) is a robust and excellent tool for assessing ischemia. So far, however, no methodology has been established to distinguish truly reduced MFR due to microvascular dysfunction or three-vessel coronary disease (CAD) from seemingly impaired MFR due to inadequate adenosine response. Conversely, for cardiac stress magnetic resonance (CMR) the adenosine induced splenic switch-off (SSO) sign has been proposed as a potential marker for adequate adenosine response. Purpose: We assessed the feasibility of detecting SSO in adenosine stress 13N-ammonia PET MPI using SSO in CMR as the standard of reference. Methods: 50 patients underwent simultaneous PET MPI and CMR on a hybrid PET/MR device with co-injection of 13N-ammonia and a gadolinium-based contrast agent during rest and adenosine-induced stress. In CMR, SSO was assessed qualitatively and quantitatively by calculating the ratio of the peak signal intensity of the spleen during stress over rest (SIR). Similarly, in PET MPI the splenic signal activity ratio (SAR) was calculated as the proportion of the maximal standard uptake value of the spleen in stress and rest. Additionally, MFR was quantified in PET MPI. Results: Visual SSO in CMR was present in 37 (74%) patients, whereas 13 patients had no SSO. The median SIR in CMR was significantly lower in patients with visual SSO compared to patients without visual SSO (0.57 [IQR 0.49–0.62] vs. 0.89 [IQR 0.76–0.98]; p<0.001). Similarly, median SAR in PET was significantly lower in patients with visual SSO in CMR compared to patients without visual SSO (0.4 [IQR 0.32–0.45] vs. 0.8 [IQR 0.47–0.98]; p<0.001). SIR correlated significantly with SAR (r=0.4, p<0.05). Mean MFR was significantly higher in patients with visual SSO compared to patients without visual SSO (3.38±0.86 vs. 2.53±0.84; p<0.05). Conclusion: Similarly to CMR, SSO can be detected in 13N-ammonia PET MPI. This might help distinguish adenosine non-responders from patients with truly impaired MFR due to microvascular dysfunction or multivessel CAD. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation (SNSF)